The influence of the concentration on the spectra and kinetics of phosphorescence of acenaphthene dissolved in glassy toluene at 77 K - N. V. Zhdanova; I. V. Gadzhialieva (Вестник Северо-Кавказского федерального университета, 2022)
There is a view on the specters and kinetics of acenaphthene phosphorescence in glass-like toluene under 77 к for solution concentrations ranging from 10-3 М. As for the concentrations above 5×10-2 М there has been detected a long wave shift in the specter, which can not be explained through directed migration of triplet excitation. Certain reasons for the effect have been discussed.